1999
DOI: 10.1038/sj.pcan.4500278
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-mediated gene transfer in dog prostate: a preclinical study of a relevant model system for gene therapy of human prostatic cancer

Abstract: This present study evaluates the potential of adenovirus-mediated gene transfer (AMGT) to the prostate of normal laboratory beagles. Many morphological and histological similarities can be noted between dog and human prostate. Moreover, dogs can spontaneously develop prostate cancer with a clinical and biological outcome identical to that in man. Firstly we showed the capacity of human adenovirus to infect canine prostatic cells in vitro. Secondly, we injected transrectally in the dogs' prostates 2610 9 plaque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…A previous study that administered a replication-deficient adenovirus vector into the prostate gland of normal dogs at a similar dose to the one we used here showed no local (urinary system) or systemic toxicity associated with the adenovirus. 31 Expression of the transduced reporter was seen exclusively in prostatic epithelial cells, and the dogs had no episodes of fever, suggesting minimal distribution of the adenovirus outside the target tissue. 31 We similarly saw no toxicity that was attributable to the adenovirus vector, and overall, the data show that intratumoral Ad-FasL therapy was extremely safe.…”
Section: Discussionmentioning
confidence: 95%
“…A previous study that administered a replication-deficient adenovirus vector into the prostate gland of normal dogs at a similar dose to the one we used here showed no local (urinary system) or systemic toxicity associated with the adenovirus. 31 Expression of the transduced reporter was seen exclusively in prostatic epithelial cells, and the dogs had no episodes of fever, suggesting minimal distribution of the adenovirus outside the target tissue. 31 We similarly saw no toxicity that was attributable to the adenovirus vector, and overall, the data show that intratumoral Ad-FasL therapy was extremely safe.…”
Section: Discussionmentioning
confidence: 95%
“…The dog is the only nonhuman species in which spontaneous prostate cancer occurs frequently 521, 711, 712. Prostate cancer in dogs is aggressive clinically, with frequent metastases to regional lymph nodes, lung, and bone 713, 714.…”
Section: 0 Goalsmentioning
confidence: 99%
“…That study showed the capacity of human adenovirus to infect canine prostate cells and constituted the first evaluation of adenovirus‐mediated gene transfer in dog prostate. It will provide a basis for the gene therapy treatment of prostate cancer patients 712…”
Section: 0 Goalsmentioning
confidence: 99%
“…First, the dogs may have previously been in contact with human adenovirus. The second possibility is that CAV‐2‐specific antibodies, induced by CAV‐2 vaccination performed on all dogs in France, recognise antigenic epitopes carried by both human and canine adenoviruses37.…”
Section: Discussionmentioning
confidence: 99%
“…One pair of primers was used in a PCR assay to detect the presence of human adenoviral DNA:OTG111 (ATGACTTTTGAGGTGGATCCCATGGA) and OTG 222 (GCCGAGAAGGGCGTGCGCAGGTA). These primers generated a fragment of 134 bp, corresponding to a consensus region of the gene encoding for the hexon protein of human adenoviruses37. All PCR procedures were performed as previously described35, 36.…”
Section: Methodsmentioning
confidence: 99%